Amorphized cellulose as filler in biocomposites based on poly(ɛ-caprolactone). (15th March 2015) - Cocca, M.; Avolio, R.; Gentile, G.; Di Pace, E.; Errico, M.E.; Avella, M.
Highlights: Amorphized cellulose particles (AC) were tested as fillers in PCL based composites. Using AC, break elongation of composites was preserved also at high filler contents. AC induced a low nucleating effect on the isothermal crystallization of PCL. AC induced a low increase of the water vapor permeability of composites. AC accelerated the soil burial degradation kinetic of composites. Abstract: Amorphous cellulose particles, obtained through a solvent-free mechano-chemical process, have been tested for the first time as a potential filler for biodegradable composites based on poly(ɛ-caprolactone) (PCL). Commercial cellulose fibers have been also tested for comparison. An effective interfacial strategy based on a compatibilizing agent, a modified PCL, has been used to improve the polymer/filler interfacial adhesion. Composites have been tested through physico-mechanical characterizations and soil burial degradation tests, in order to evaluate the influence of cellulose structure and morphology and polymer/filler interfacial adhesion on the final properties of the realized materials. The use of the amorphous cellulose particles combined with the presence of a suitable interfacial agent has allowed to modulate relevant technological properties of the realized composites, such as tensile and thermal properties, water absorption, water vapor transmission rate and biodegradation kinetic.